Agriculture: Transition Buffer or Black Hole? A Three-State Model of Employment Dynamics - Alexandru Voicu (Institute for the Study of Labor (IZA), 2003)
We analyze the effect of land reform legislation on labor market dynamics in the Romanian economy. We show that the agricultural sector, a source of precarious employment, has become an absorbing state for certain categories of workers who lost their jobs in the nonagricultural sector. A random utility model is used to represent individuals? sequential labor market decisions. The resulting multivariate probit model is estimated using Markov chain Monte Carlo methods.
Keywords: J23; C35; C11; C15; C33; 330; labor force participation; three-state dynamic model; multivariate probit; Markov chain Monte Carlo; transition economy; land reform; Agrarreform; Landwirtschaft; Übergangswirtschaft; Beschäftigungseffekt; Schätzung; Ukraine